PERTUMBUHAN AWAL DAN EVAPOTRANSPIRASI AKTUAL TANAMAN TOMAT (Lycopersicum esculentum Mill) PADA BERBAGAI UKURAN AGREGAT INCEPTISOLS - Hasanah, Uswah; Ardiyansyah, Ardiyansyah; Rosidi, Ayip (Agroland: Jurnal Ilmu-ilmu Pertanian, 2010)
Soil structural unit distribution in seedbed tilth can affect plant growth, in part by modifying hydraulic properties and resistance of soil. The purpose of the study was to determine the early growth and actual evapotranspiration of tomato plant as influenced by various soil aggregate sizes. Soil bulk density, shoot and root dry matter, root length, and evapotranspiration of tomato plant grown on <0.5 mm, 0.5.0-2.0 mm, 2.0-4.0 mm, and >4 mm of aggregate sizes were determined 5 weeks after planting. The bulk density consistently decreased with increasing aggregate size. Shoot dry matter in the 0.5-2.0 mm aggregate size was 3.34 g which was twice and 1.3 times greater than that in 2.0-4.0 mm and < 0.5 mm aggregate size, respectively. Similar trend was also shown by root dry matter and root length. The root length was greatly reduced in 2.0-4.0 mm aggregate size. Actual evapotranspiration in <0.5 mm was 28.56 cm slightly higher than in 0.5-2.0 mm aggregate size.